Los valores en el desarrollo socioafectivo en los niños de educación inicial - Lovato Yupanqui, Verónica Pilar (2017)
This research was carried out with the objective of determining the values in the educational community that affect the socio-affective formation processes in the children and initial education of the "Luis Napoleón Dillon" school during the academic year 2016-2017. This process was compiled theoretical and conceptual foundations about socio-affective relations and learners´ values that allow to apply within the educational community, then with the help of research techniques such as; the interview and the survey inquired about the values they are incurring in the field of education, in the family environment for the training of infants, later with the analysis obtained a diagnosis of the socio-affective values of children was elaborated; It should be emphasized that it is important to mention that today values are being lost in educational institutions, and it is suggested that all values be applied to the children of initial education, since when they grow up they will help them to live better wherever they grow, values such as; friendship, understanding, tolerance, patience, solidarity and respect are essential for the healthy development of children, the main factor that helps to develop values is the Family from the home parents should instill the values through their example, children learn from their parents, how to relate to others, to ask for things, to share the table, to seat, to cooperate, to help others , to defend, to complain, to tolerate and accept. If parents do not have patience with their child, the parents´ responsibility is to teach values to their children which is important. At school, teachers are the second parents because we seek safety and harmonious socialization with peers inside and outside the classroom. The research was new for what that, represents that parents and teachers will see the progress of their children's values in the educational field that is important part of their daily life, since it would help each day to be better and gaining new knowledge.